Letter of condolence from Alexander Baczewski to Max Bredig - Baczewski, Alexander (1944)
Letter of condolence regarding the death of Georg Bredig (1868-1944) from Alexander Baczewski to Max Albert Bredig (1902-1977).
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Chemists; Condolence notes; Baczewski, Alexander